Penerapan Pembelajaran Blended Learning Berbasis Gawai pada Masa Pandemi Covid-19 - Adisel Adisel; Suryati Suryati; Sukarno Sukarno; Ahmad Gawdy Prananosa (JOEAI:Journal of Education and Instruction, 2021)
The purpose of this study is to describe the application of device-based blended learning and to analyze the factors that influence the process of implementing device-based blended learning in the Social Sciences Department of STKIP PGRI Lubuk Linggau. This research uses a qualitative approach, where this research is carried out in a natural, reasonable situation and a real setting (natural setting). The type of research used in this research is a case study. The results of the study, the policy for the use of blended learning has been set in the learning guidelines of STKIP PGRI Lubuk Linggau. So that its implementation has been shaded by the Institute so that it does not run alone. Human resources are one of the influential factors in the implementation of blended learning. In conclusion, the application of blended learning during the Covid-19 pandemic in the social studies department at STKIP PGRI Lubuk Linggau was carried out in accordance with the learning guidelines under the auspices of the institution. and learning support infrastructure. Keywords: Covid-19 Pandemic, Blended Learning